Cross sectional quality of life analysis among diabetic foot ulcer patients - Abdul Rahman, Mohd Norhisham Azmi; Ngadnan, Nur Ilham Alia; Fauzi, Muhammad Aiman; Ungku Ismail, Ungku Sarah Syahidah; Mahno, Noor Ezmas; Ahmad, Azrin Waheedy; Othman, Ahmad Faidzal (The Editorial Committee of Annals of Vascular Diseases, 2018)
Background Foot ulcer is one of the most serious complications associated with diabetes mellitus that could result with a disability and impairment of health related quality of life. Objectives The main objective is to analyse the quality of life (QoL) among diabetic foot ulcer patients. Secondary objective is to identify factors adversely affected QoL in this population. Methodology Diabetic patients with evidence of diabetic foot ulcer (DFU) attending outpatient orthopaedics and general surgical clinic of Hospital Tengku Ampuan Afzan, Pahang, Malaysia were recruited into this study. A set of validated SF-36 questionnaire was employed to evaluate the health-related quality of life for each patient.Favourable ethical approval obtained from Medical Research and Ethics Committee (NMRR registration no. 17-1520-36332). Results There is a slightly higher proportion of female among the 104 respondents with DFU with a predilection among the lower income group. Majority presented with Wagner stage 2 and 3. More than half underwent amputation previously. DFU affected physical health worse than the mental health. Increasing age, low socioeconomic status, presence of comorbidities, major amputation, ulcer at the forefoot and wheelchair usage adversely affected the physical health aspects. Interestingly, smoker seems to score better on the mental health aspect of the quality of life. Conclusion Diabetic foot ulcer affected physical health aspect much more than mental health aspect within the context of the quality of life.